THE ROLE OF CAPITAL IN STRENGTHENING THE RESOURCE BASE OF BANKS (Web of Teachers: Inderscience Research, 2025)
In today’s financial markets, where competition is intensifying, ensuring the sustainable operation of commercial banks, especially private banks, is of paramount importance. Private banks are among the key institutions stimulating economic growth by supporting investment processes in the national economy, attracting the idle funds of the population and business entities, and directing them efficiently.